The Praeger handbook of human resource management - Gilley, Ann Maycunich; Praeger Publishers; Gale Group (Westport, Conn. Praeger, 2009)
HR experts cover the personnel waterfront from hiring right to creating policies to laying the foundation for profitability and fun.
v. 1, pt. 1. Human resource practices -- v. 2, pt. 2. Organizational issues ; pt. 3. General HR issues ; pt. 4. HR policy ; pt. 5. Checklists and tools ; pt. 6. Resources.
Electronic reproduction.
Keywords: Personnel management; Electronic books